The Effect of Social Media on Mental Wellbeing: The Good and the Bad - Akram, Muhammad; Umaru, Isaac John; Aslam, Nosheen; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammed; Mahmood, Abid (Darul Yasin Al Sys, 2025)
Social media has evolved into a central platform for interpersonal communication and a powerful source of information within contemporary culture. While earlier generations were less accustomed to integrating technology and social media into daily life, current users actively embrace these platforms. Beyond facilitating social connections and networking opportunities, social media also serves as a tool for raising awareness and promoting various causes. However, these benefits are counterbalanced by potential negative effects on users’ emotional well-being. This paper critically examines the impact of social media on mental health, focusing on issues such as social media addiction, anxiety, depression, and self-esteem. It explores how excessive media use and social comparison contribute to psychological distress, highlighting the importance of user responsibility. Ultimately, the discussion advocates for a balanced approach to social media engagement that safeguards mental health while leveraging its positive potentials.